Antioxidant, antibacterial, and anti-adhesive activities of biosurfactants isolated from Bacillus strains. (July 2019) - Giri, S.S.; Ryu, EC.; Sukumaran, V.; Park, S.C.
Abstract: Biosurfactants are surface-active compounds that display a range of physiological functions. The present study investigated the antioxidant, antimicrobial, and anti-adhesive or anti -biofilm potential of biosurfactants isolated from Bacillus subtilis VSG4 and Bacillus licheniformis VS16. The antioxidant activity of the biosurfactants was studied in vitro using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl radicals. At 5 mg/mL of the biosurfactant concentration, the scavenging of DPPH and hydroxyl radicals was found to be between 69.1-73.5% and 63.3-69.8%, respectively. The biosurfactants also displayed significant antibacterial activities against both Gram-positive and Gram-negative bacteria. The anti-adhesive activities of the biosurfactants were evaluated against Staphylococcus aureus ATCC 29523, Salmonella typhimurium ATCC 19430, and Bacillus cereus ATCC 11778. The biosurfactants exhibited anti-adhesive activity, even at concentrations of 3-5 mg/mL. Moreover, both biosurfactants displayed notable anti -biofilm activities with a biofilm eradication percentage ranging from 63.9 to 80.03% for VSG4 biosurfactant, and from 61.1-68.4% for VS16 biosurfactant. Furthermore, VSG4 biosurfactant exhibited emulsification and surface tension stability over a wide range of pH (4-10) and temperature up to 100 °C. These results show that VSG4 and VS16 biosurfactants can be potentially used as natural antioxidants, antimicrobials, and/or anti-adhesive agents for food and biomedical applications. Highlights: Biological potential of biosurfactants derived from two Bacillus strains were evaluated. Biosurfactants exhibited DPPH & hydroxyl radical antioxidant activities. Promising antibacterial & anti-adhesive activities were found in both biosurfactants Biosurfactants showed a satisfactory antibiofilm effect against tested bacteria.